Pendampingan Pembelajaran Fiqih Dengan Memanfaatkan Media ICT Bagi Siswa SDN 1 Sukorejo di Desa Sukorejo Kecamatan Sukorejo Kabupaten Ponorogo - Tiara, Elsa Nindhy; Witasari, Rinesti (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The writing of this article was motivated by the tendency of a lack of innovation in Fiqh learning in elementary schools. Some students are less interested in learning that is dominated by lectures. Based on these problems, researchers conducted research using ICT learning media. The research aims to increase students' interest in learning fiqh learning material at SD Negeri 1 Sukorejo, Sukorejo village, Sukorejo subdistrict. This learning assistance uses Power Point learning media and also animated videos. The research results show that the application of ICT learning media can increase students' interest and attractiveness in learning. Students look enthusiastic and happy when taking part in fiqh learning. Data collection in this research used the ABCD (Asset-based community development) data method. The test results show that interesting learning media makes it easier for students to understand the material and are more enthusiastic about learning, thereby improving learning outcomes.